Immune Activation in Functional Dyspepsia: Bystander Becoming the Suspect - Ceulemans, Matthias; Jacobs, Inge; Wauters, Lucas; Vanuytsel, Tim (Frontiers in Neuroscience, 2022)
Disorders of gut-brain interaction (DGBI), formerly termed functional gastrointestinal disorders (FGID), are highly prevalent although exact pathophysiological mechanisms remain unclear. Intestinal immune activation has been recognized, but increasing evidence supports a pivotal role for an active inflammatory state in these disorders. In functional dyspepsia (FD), marked eosinophil and mast cell infiltration has been repeatedly demonstrated and associations with symptoms emphasize the relevance of an eosinophil-mast cell axis in FD pathophysiology. In this Review, we highlight the importance of immune activation in DGBI with a focus on FD. We summarize eosinophil biology in both homeostasis and inflammatory processes. The evidence for immune activation in FD is outlined with attention to alterations on both cellular and molecular level, and how these may contribute to FD symptomatology. As DGBI are complex and multifactorial conditions, we shed light on factors associated to, and potentially influencing immune activation, including bidirectional gut-brain interaction, allergy and the microbiota. As specific anti-inflammatory therapies could offer renewed hope for at least a subset of DGBI patients, crucial studies that reveal a therapeutic benefit of treatments targeting immune activation are discussed. Lastly, we explore the future directions for DGBI research that could advance the field. Taken together, emerging evidence supports the recognition of FD as an immune-mediated organic-based disorder, challenging the paradigm of a strictly functional nature.